Code Switching Analysis in English Education Content on YouTube - Dzulfikar, Ahmad; Jabu, Baso; Korompot, Chairil Anwar (Journal of Excellence in English Language Education, 2025)
This study aims to determine the frequency of code-switching, the types of code-switching, and the accuracy of the message that occurs within an educational video. The research method used is the qualitative approach. The research uses a descriptive research method that involves the analysis of three chosen videos uploaded on YouTube. The research will find the frequency of code switch occurrence, types of code-switching, and how the message is conveyed correctly when the code switch occurs. The research found that there is an average of 35 to 45 code switches that occur in the first 5 to 6 minutes of each video and each of those occurrences consisted of three types of code switches which are inter-sentential code switch, intra-sentential code switch, and extra-sentential code switch. The messages or information that the content creator tries to convey through the content they create are understandable. In conclusion, code switches are frequently used in educational content on YouTube and are consisted to three types of code switches with messages that are understandable to the viewers of the content.